Pendekatan Agama Membaharui Kondisi Psikologis Siswa Terindikasi Nomophobia - Maria Patricia Tjasmadi (Proceedings of The ICECRS, 2019)
The development of technology communication in the era of the Industrial Revolution 4.0 has become epidemic and has not only given a negative impact on youth communities in big cities but also to all residents in the Indonesian regions. When communication technology began to develop in Indonesia, it was assumed not to be considered as causing problems in academic values, morals, and student faith, so teachers and spiritual counselors did not feel the need to anticipate. Nowadays, dependence on cellphones facilitating digital communication and online games become difficult to overcome and has develops nomophobia. Based on the WHO reference, the Indonesian government has declared that since 2018 the addiction to online games has enters the category of psychiatric disorders. This research is an attempt to find a solution to overcome the disorders, so that questions about psychological conditions of students indicated with nomophobia can be renewed through religious approaches. Religion has a basic function where its essence be able to direct views or orientation, motivate and help humans tobehave properly according to their beliefs. Results of this study are expected benefiting teachers and observers of Education in the era of the 4.0 Industrial Revolution in overcoming the problem of nomophobia which can seize the human health.